Modeling of an array of amperometric microbiosensors - Ivanauskas, Feliksas; Baronas, Romas; Kulys, Juozas; Sapagovas, Mifodijus (Lietuvos matematikos rinkinys, 2004)
This paper presents a two-dimensional-in-space mathematical model of a sensor system based on an array of enzyme microreactors immobilised on a single electrode. The model is based on the diffussion equations containing a non-linear term related to the Michaelis–Menten kinetics of the enzymatic reaction. Using computer simulation the influence of the geometry of the enzyme microreactors on the biosensor response was investigated. The digital simulation was carried out using the finite difference technique.
Keywords: reaction-diffusion; mathematical modelling; biosensor; microreactor